Pengaruh Motivasi, Persepsi Return, dan Kemajuan Teknologi Informasi terhadap Pertimbangan Investasi Syariah dengan Perilaku Keuangan sebagai Variabel Moderasi - Riana Adhistyaning Kusuma; Luqman Hakim (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The growth in the number of Islamic investors has doubled compared to the end of 2020. However, there are still many students who have not allocated their funds to invest, students only save funds in the form of savings. This research aims to determine the effect of motivation, return perception, and advances in information technology in considering investing in the Islamic capital market with financial behavior as a supporter of each variable. The research method in this research uses quantitative research with data collection techniques through the distribution of online questionnaires. This study used a sample of 144 respondents, and analyzed using the Structural Equation Modeling (SEM) technique which is a derivative of the WarpPLS 7.0 application. The results of the analysis in this research state that motivation, perceived returns and advances in information technology have a direct and significant effect. In addition, financial behavior cannot moderate the motivation and perception of return on sharia investment considerations. Financial behavior can moderate the perception of return on investment considerations for state university LPTK students in Indonesia